2020
DOI: 10.1001/jamanetworkopen.2019.19185
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Out-of-Pocket Costs for Robotic Cancer Surgery in US Adults

Abstract: IMPORTANCE Expensive technologies-including robotic surgery-experience rapid adoption without evidence of superior outcomes. Although previous studies have examined perioperative outcomes and costs, differences in out-of-pocket costs for patients undergoing robotic surgery are not well understood. OBJECTIVE To assess out-of-pocket costs and total payments for 5 types of common oncologic procedures that can be performed using an open or robotic approach. DESIGN, SETTING, AND PARTICIPANTS A retrospective, cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…8 Robotic surgical platforms have been used successfully for years for complicated procedures, many in complex oncological situations, which can benefit from minimally invasive surgery advantages. 9 Gynecological patients with benign (i.e., fibroids) or malignant disease or comorbidities (i.e., obesity) no longer have to be subjected to open laparotomy, but instead benefit from both surgical and post-surgical advantages offered by robotic minimally invasive surgery. 6,7,10 Once laparoscopic assisted hysterectomy techniques began being used, patient recovery and satisfaction were remarkably improved compared to prior patients receiving either the AH or VH procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 Robotic surgical platforms have been used successfully for years for complicated procedures, many in complex oncological situations, which can benefit from minimally invasive surgery advantages. 9 Gynecological patients with benign (i.e., fibroids) or malignant disease or comorbidities (i.e., obesity) no longer have to be subjected to open laparotomy, but instead benefit from both surgical and post-surgical advantages offered by robotic minimally invasive surgery. 6,7,10 Once laparoscopic assisted hysterectomy techniques began being used, patient recovery and satisfaction were remarkably improved compared to prior patients receiving either the AH or VH procedures.…”
Section: Discussionmentioning
confidence: 99%
“…There have been barriers to robotic surgical platforms in the past; namely the expense of the platform for hospitals and patient billing, training of users, and justification of use via clinical evidence of benefit. 4,7,9 The robotic systems have been in larger institutions for 20 years and in gynecological use for 15. 4 Short and long term clinical benefit data for surgeons and patients have been established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent retrospective, propensity score-weighed analysis using insurance claims from the MarketScan database showed that the robotic approach was associated with lower out-of-pocket costs for five types of common oncological procedures compared to open surgery [ 66 ].…”
Section: Benefits and Limitationsmentioning
confidence: 99%